2010
DOI: 10.1016/j.socscimed.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Translating HIV interventions into practice: Community-based organizations’ experiences with the diffusion of effective behavioral interventions (DEBIs)

Abstract: Efficacious behavioral interventions developed to address the spread of HIV/STIs are currently being disseminated in the USA through a national diffusion program (DEBI) spearheaded by the Centers for Disease Control and Prevention (CDC). Understanding how interventions are translated to real world settings is necessary to further scientific knowledge of this process and to facilitate future translation efforts in public health. Prior studies have begun to elucidate how agencies translate behavioral interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…The present study grew out of a broader investigation that aimed to improve our understanding of the adoption, adaptation, and implementation of HIV behavioral interventions [41]. The broader study focused on concepts in the innovative-decision process in Rogers's diffusion of innovations theory [12], which are also reflected in the ADAPT framework [41, 42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study grew out of a broader investigation that aimed to improve our understanding of the adoption, adaptation, and implementation of HIV behavioral interventions [41]. The broader study focused on concepts in the innovative-decision process in Rogers's diffusion of innovations theory [12], which are also reflected in the ADAPT framework [41, 42].…”
Section: Methodsmentioning
confidence: 99%
“…The broader study focused on concepts in the innovative-decision process in Rogers's diffusion of innovations theory [12], which are also reflected in the ADAPT framework [41, 42]. …”
Section: Methodsmentioning
confidence: 99%
“…Whereas couples therapy is quite different from incorporating friends into alcohol interventions, this area of research provides a foundation for prevention approaches that incorporate close others over individual treatment. For example, research on HIV prevention among adolescents has examined the inclusion of friends in interventions (Dolcini et al, 2010; Fang et al, 1998; Harper et al, 2012; Morrison et al, 2007). In line with the present findings, Morrison et al (2007) found HIV prevention among adolescents to be moderated by friendship closeness.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisors are intended to help contribute to the fidelity of the program across providers by helping individual providers deliver the program appropriately. Several studies suggest that staff fluctuations, especially turnover, have a significant impact on organizations’ ability to implement RESPECT (3032). Consequently, this program provides an appropriate context for examining the influence of organizational capacity, especially human resources, on EBI implementation.…”
Section: The Current Researchmentioning
confidence: 99%